(untitled) (Research, Society and Development, 2023)
Boron (B) is one of the most important nutrients in olive growing, and in Brazil there is still a lack of studies that evaluated the effect of fertilization with B for olive trees. Thus, the aim of the study was to verify whether soil and foliar boron fertilization influenced the B leaves content, during the flowering period and the beginning of fruiting. Two olive groves were evaluated in the central region of the state of Rio Grande do Sul, in Caçapava do Sul (CS) and São Gabriel (SG), adopting a bifactorial experimental design with soil B doses (0, 25, 50 and 100 g) and presence/absence of foliar B. Boron contents were quantified before fertilization (T0), after soil fertilization (T1) and after foliar fertilization (T2). Fertilization with B in the soil and foliar did not increase the levels of foliar B. However, it was observed that B concentration decreased in T1 (flowering) compared to T0 (pre-flowering), with a reduction in mature leaves of CS and SG of approximately 45% and 34%, respectively. Boron concentration increased again in T2 (initial fruit development), regardless of fertilization, statistically differing from T1, in both olive groves. Higher B content was observed in CS in all evaluated periods, possibly being associated with higher concentration of B in the soil. The present study reinforces the hypothesis that in olive trees there is remobilization of B from the leaves to attend the metabolic needs of reproductive structures, especially in floral development.